Marine and coastal protected areas : - Salm, Rodney V. (International Union for Conservation of Nature and Natural Resources, 2000)
This is a new edition of the classic textbook on marine protected area (MPA) management in the tropics, originally produced as an output of the Bali World Parks Congress in 1982. Approaches to planning and managing MPAs have evolved considerably. Major advances include innovative financing mechanisms, partnerships with the private sector and NGOs, and collaborative management between government and coastal communities